Hemodynamic, hemostatic, and endothelial reactions to acute psychological stress in depressed patients following coronary angiography. (23rd May 2013) - Plourde, Annik; Lavoie, Kim L.; Ouellet, Karine; Carroll, Douglas; Ring, Christopher; Bacon, Simon L.
Abstract Although there is evidence that depression is associated with an increased risk for coronary artery disease (CAD), the mechanisms underlying this association remain unclear. This study examined the association between depression and hemodynamic, hemostatic, and endothelial responses to psychological stress. Seventy‐two postcoronary angiography patients completed a mental stress task. Blood pressure, heart rate, and impedance cardiography were recorded at rest and during the task. Blood samples were taken at the end of rest and immediately after the task. Depression was evaluated using the Diagnostic Interview Schedule Self‐Administered (DISSA). In total, 21% of the participants were depressed. Analyses revealed that depression was associated with blunted pre‐ejection period stress reactivity and with increased platelet factor 4 reactivity. These data provide potential mechanistic pathways linking depression to increased CAD.